Zinc fertilization effect on productivity and nutritional status of rice (Oryza sativa) in North-east India - SINGSON, HOINEICHONG; I, RAMKRUSHNA G; LAYEK, JAYANTA; DAS, ANUP; PANDE, RACHNA; VERMA, B C; SHAHANE, A A; SHIVAY, Y S (The Indian Journal of Agricultural Sciences, 2021)
The highest increase in grain Zn concentration was observed with foliar Zn application followed by ZnCU and least with soil Zn application. Among various Zn fertilization options, 3% ZnCU and soil application of Zn (5 kg/ha) was found most promising for improvement in growth attributes, grain and straw yields and Zn, N, P, K and S concentrations in rice grain. Therefore, Zn application through 3% ZnCU to rice is a recommendable option for improving rice productivity and its nutritional status in NEH region of India.